THE INFLUENCE OF ELECTORAL PROGRAM OF VOLLEYBAL AND BASKETBAL ON THE TRANSFORMATION BIOMOTORICALY ABILITY STUDENTS - Vidran Kljajević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
A sample of this study were composed of a third grader in high school that are at the beginning of this study was 17 years old ± 6 months. The survey covered a total of 161 subjects, divided into two groups: experimental (E), which consisted of 78 subjects, and control (K), which consisted of 83 subjects. Experimental group of subjects was realized in the electoral program odbojeke And half the electoral program of basketball in the second half. A control group of subjects practiced the''standard''teaching program which included content from athletics, gymnastics, rhythm and sports games. The study was conducted under the system of pedagogical experiment with parallel groups and the changes that have taken place under the influence of the implemented curriculum were monitored in space and the ability biomotoričkih antrometriskih dimension and posit their level is dijagnostofikovan at the beginning (initial) and at the end of the study (final). In this paper, We'll look review of the results of this study which were obtained in space biomotoričkih ability examinees. The level of their biomotoričkih ability was tested using a battery of 11 motor tests. With this battery are evenly covered all areas of latent motor skills, and the mechanisms responsible for resolving eaten motor tasks.